Employment of highly-skilled migrants during the pandemic: Focus on internal migration in Indonesia. (March 2023) - Arifin, Evi Nurvidya; Ananta, Aris
This article examines whether highly-skilled migrants (HSMs) have better employment prospects compared to low-skilled migrants (LSMs), highly-skilled non-migrants (HSNMs) and low-skilled non-migrants (LSNMs) during the unsettling time of the COVID-19 pandemic. This question was explored by focusing on internal migration in Indonesia utilizing the August 2020 National Labor Force Survey, which includes several pandemic-related information. The study examined employment in terms of working status, change in hours worked and change in income. The results indicate that having high skills was very important in coping with the disruptions in the labor market, regardless of the migration status. The highly-skilled migrants were the second best (after the highly-skilled non-migrants) in coping with the crisis. As this study focused on migration, future research should focus more on short-term mobility, such as commuters, who were likely to have been more disadvantaged by mobility restrictions during the pandemic.